The Consequences of Disclosing Key audit Matters on Investors' Judgment and Decision-making - Zohre Heydari; Shahnaz Mashayekh (پژوهش‌های تجربی حسابداری)
In 2022, the disclosure of Key Audit Matters (KAMs) became mandatory to enhance the informational value of the auditor’s report. These disclosures aim to provide valuable information for investor decision-making, enabling them to better evaluate earnings benchmark performance. Consequently, this research investigates how disclosing KAMs influences investors’ judgment and decision-making. The study employed a 2x2 between-groups factorial design. The independent variables were the type of audit report and earnings benchmark performance, while the dependent variable was investors’ valuation judgment. Participants consisted of 176 individuals (96 professionals and 80 non-professionals), with each group randomly and independently assigned to one of four equally sized subgroups. The research findings indicate that Key Audit Matters influence the judgment and decision-making of professional investors, reducing their willingness to invest, but do not impact the judgment and decision-making of non-professional investors. Earnings benchmark performance affects the valuation judgment of both groups, with no interaction observed between earnings benchmark performance and Key Audit Matters. Notably, these findings offer valuable insights for various stakeholders, including standard setters, issuers, auditors, and investors